A gain-of-function study of amelioration of pentylenetetrazole-induced seizures by endogenous prostaglandin D2. (1st November 2018) - Kaushik, Mahesh K.; Aritake, Kosuke; Cherasse, Yoan; Sharma, Rahul; Urade, Yoshihiro
Highlights: We used H-PGDS Tg mice that overexpress human hematopoietic prostaglandin (PG) D2 synthase (H-PGDS) enzyme. H-PGDS Tg mice produce high basal and seizure-induced PGD2, apparent by increased urinary tetranor-PGDM (PGD2 metabolite). Pentylenetetrazole-induced seizures were ameliorated in H-PGDS Tg mice. Seizure onset latency increased and a decrease in generalized tonic-clonic seizures and seizure spikes was observed. No change in PGE2 metabolite (tetranor-PGEM) suggests that the decrease in seizure intensity was due to increased PGD2 . Abstract: We previously showed that knockout mice of hematopoietic prostaglandin (PG) D synthase (H-PGDS) produce less PGD2 to exacerbate pentylenetetrazole (PTZ)-induced seizures. Here, we adopted a gain-of-function strategy and used transgenic mice that over-express human H-PGDS enzyme, to elucidate the role of overproduction of endogenous PGD2 in PTZ-induced seizures. H-PGDS-transgenic mice showed the elevated level of a urinary metabolite of PGD2, tetranor-PGDM, 3.3- and 2.8-fold higher than the wild-type littermates under the basal condition and after the PTZ administration, respectively, without significantly changing the urinary concentration of a PGE2 -metabolite, tetranor-PGE2 . The intensity of PTZ-induced seizures was decreased in H-PGDS-transgenic mice as evident by the increased seizure onset latency, and a decrease in total duration of generalized tonic-clonic seizures and a total number of EEG seizure spikes during the postictal period (84 s, 17 s, and 5.3/min, respectively), as compared to wild-type mice (53 s, 24 s, and 12.6/min, respectively). These results indicate that overproduction of endogenous PGD2 decreased PTZ-induces seizures.